Recreational Fishing Effort and How Management Actions Can Affect It—Part 2: Literature and a Case Study. - Edward Camp; Michael S. Allen; Thomas T. Ankersen; Savanna Barry; Mark W. Clark (EDIS, 2023)
Recreational fishing, crucially important to Florida’s economy and ecosystems, can be affected by management decisions. Decisions that change the allowable harvest or the type of access to certain fishing areas are often expected to have strong effects on fishing effort, but the outcome of these actions is not always obvious. To provide greater insight into what may happen to fishing effort after management decisions, we describe case studies from the North American fisheries literature, some Florida-specific. These illustrate that the same or similar management actions (e.g., a more restrictive harvest policy) can have opposite effects on total fishing effort depending on the specifics of the case. We use this information as well as additional fisheries theory to explore a specific case study—what might happen if special harvest or access regulations were applied to a popular but ecologically and environmentally sensitive habitat—the St. Martins Marsh Aquatic Preserve in Citrus County, Florida.